(untitled) (Herald of Journalism, 2025)
The research aims to trace the transformation of Kazakhstan’s media image in China and to identify how different types of media contribute to shaping its regional role within South-South cooperation. National image constitutes a core element of a country’s soft power. A favorable national image enhances national cohesion domestically while boosting international competitiveness externally. Concurrently, due to shifts in the international landscape, ideological confrontations, and cultural disparities, the construction of national images by external actors faces cognitive biases and communication challenges. As a crucial source of "other-oriented perspectives," media coverage plays a pivotal role in shaping national images. The methodology of this research is to employing Critical Discourse Analysis and Framing Theory, this study systematically examines the evolution of narrative strategies in China’s mainstream media, market-oriented media, and social media regarding Kazakhstan from 2004 to 2024. The analysis identifies distinct phased characteristics in China-Kazakhstan relations as constructed through media narratives, manifesting three distinct phases: the Energy Cooperation Period (2004–2013), the Strategic Upgrading Period (2013–2022), and the Multi-Dimensional Deepening Period (2022–2024).Throughout this progression, Kazakhstan’s national image has undergone a concomitant transformation. The results of this study show that Kazakhstan’s national image has shifted from being framed primarily as an energy partner to a multidimensional strategic actor. Official media reinforced strategic legitimacy through "Belt and Road" label anchoring and policy coordination narratives, while social media activated public emotional resonance via low-context symbols, forming a "high-low context complementary" communication paradigm. Furthermore, the media image and actual national profile exhibit bidirectional co-construction – Chinese media not only reflect Kazakhstan’s objective development but also proactively shape its regional role through strategic communication. This research provides theoretical insights into reconstructing South-South cooperation discourse through non-confrontational media narratives and offers empirical references for Kazakhstan to optimize its communication strategies toward China and engage in Global South discourse power competition.